KEBIJAKAN PEMERINTAH DALAM IMPLEMENTASI HUKUM PERLINDUNGAN ANAK DAN UPAYA PENANGGULANGANNYA TERHADAP HAK-HAK ANAK DI INDONESIA - Wulansari, S.H., M.H. (Jurnal Ilmiah Hukum: De'Jure, 2016)
Denoted phenomenon about child attracts our attention. There are many violation cases happened on child right. Therefore, in order to build ideal condition, it is needed government role to protect child right. The aim of this research is to know government policy in the implementation child protection in Indonesia, to know factors that become obstacle or problem in protecting towards child right in Indonesia and preventive and countermeasure effort to minimize violation on the child right in Indonesia. This research is analytical description and using normative juridical approach. Technique of data collection is conducted through literature study and field study. Data analysis is done through qualitative. Based on the result of research, it can be concluded that the government policy in the implementation of child right in Indonesia can be seen from government policy to build institutions which concern on child protection in Indonesia for instance there is ministry that specifically ensure child rights those are Ministry of Woman and Child Protection, Commission of Indonesia Child Protection (KPAI), Integrated Service Center Woman and Child Protection (P2TP2A), Social Bureau Woman and Child Protection (BPSAA). Factors that become obstacle and problem in protecting on child right in Indonesia are classified to be some factors; they are law substation factor, law structure and law culture. Preventive and countermeasure effort to minimize violation on the child right in Indonesia can be seen from preventive formulation in region by having organizing that arranges specifically about child right which produce Region Regulation of Child Protection, Regulation about Commission of Child Protection in region and other regulations on it. Effort preventive formulation can be made by government policy to guarantee countermeasure towards the children that become victim of violation of child right.